Isolation and characterization of plant growth-promoting bacteria from medicinal plants Java cardamom (Amomum compactum) and bitter ginger (Zingiber zerumbet) - ALMANDO GERALDI; CHRISTOPHER CLEMENT; MAYA DEWI PERTIWI; YESYI LESTARI; DHAMMARUCI HEMADHIRA PARINNATA; RIFAID NUR ARSAD; RAMA ALI SADIKIN; ARIF LUQMAN; HERI SANTOSO; ALFINDA NOVI KRISTANTI; YOSEPHINE SRI WULAN MANUHARA; ANJAR TRI WIBOWO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Geraldi A, Clement C, Pertiwi MD, Lestari Y, Parinnata DH, Arsad RN, Sadikin RA, Luqman A, Santoso H, Kristanti AN, Manuhara YSW, Wibowo AT. 2024. Isolation and characterization of plant growth-promoting bacteria from medicinal plants Java cardamom (Amomum compactum) and bitter ginger (Zingiber zerumbet). Biodiversitas 25: 2556-2564. Java cardamom (Amomum compactum) and bitter ginger (Zingiber zerumbet) are valuable medicinal plants native to Indonesia with significant economic and pharmacological importance. While their pharmacological properties have been extensively studied, little is known about the role of their endophytic bacterial communities in influencing plant growth and development. Understanding the interactions between these plants and their associated bacteria could provide insights into novel strategies to enhance their cultivation. This study investigates the potential of endophytic bacteria associated with A. compactum and Z. zerumbet in promoting plant growth. Samples were collected from leaf, rhizome, and rhizosphere soil, followed by isolation and characterization of bacterial strains. Molecular identification revealed the presence of Methylobacterium aquaticum, Paenibacillus tyrfis, Priestia megaterium strain 1, Priestia aryabhattai, and Microbacterium arthrosphaerae among the isolated strains from A. compactum, while strains isolated from Z. zerumbet included Enterobacter mori, Pr. megaterium strain 2, and Pr. megaterium strain 3. Those results demonstrated that Pr. megaterium strains exhibited strong phosphate solubilization, nitrogen fixation, and cellulolytic activity, while Pr. aryabhattai and Pa. tyrfis showed significant nitrogen fixation and cellulolytic potential. Additionally, M. aquaticum, Pa. tyrfis, and Pr. aryabhattai exhibited anti-phytopathogenic activity against Xanthomonas campestris. These findings not only highlight the diverse beneficial attributes of the isolated bacterial strains but also suggest their potential application as biofertilizers and biocontrol agents in agriculture, offering a promising avenue for sustainable farming practices.